Cybersecurity for industrial scada systems - Shaw, William T. (PennWell Books, LLC, 2020)
"Cybersecurity for SCADA Systems provides a high-level overview of SCADA technology, with an explanation of each market segment. Readers will understand the vital issues, and learn strategies for decreasing or eliminating system vulnerabilities"-- Provided by publisher
Keywords: Supervisory control systems.; Automatic data collection systems.; Data protection.; Computer security.; elektronické knihy; electronic books